“The King Whom Yahweh Your God Chooses”: Deuteronomic Kingship in a World of Sacral Kingship - Hwang, Jerry (Horizons in biblical theology, 2023)
Hebrew Bible scholars tend to dismiss Deuteronomy’s “Law of the King” (17:14–20) as a utopian construct that was never realistic and/or historical. Underlying these views, however, are certain assumptions about what is culturally plausible in a world dominated by sacral kingship. Since this is the most common form of government in human history, generalizations about the historicity of Deuteronomic kingship requires an intercultural analysis of theopolitics, divine right of kings, and separation of powers. This article sets Deuteronomic kingship in the larger context of sacral kingship in Asia, Africa, Europe, and the Americas. What then emerges is the bridging of a notable false dichotomy in scholarship – Israel’s form of sacral kingship is both distinctive as well as realistic in nature. This suggests that skepticism about the historicity of the “Law of the King” is beholden to a Eurocentric frame of reference which is also skeptical of Western-style absolute monarchy.